Relationships Between Stereotyped Movements and Sensory Processing Disorders in Children With and Without Developmental or Sensory Disorders - Gal, E.; Dyck, M.; Passmore, Anne (American Occupational Therapy Association Inc, 2010)
OBJECTIVE. Stereotyped movements (SM) are a defining characteristic of autism but are also present in children with a range of sensory and developmental disorders. We examined whether the severity of sensory processing disorders (SPD) was associated with the severity of SM and whether SPD accounted for between group differences in SM. METHOD. The Short Sensory Profile and the Stereotyped and Self-Injurious Movements Interview were administered to children with autism, intellectual disability, visual impairment, and hearing impairment and to typically developing children. RESULTS. SPD predicted the severity of SM in all samples and accounted for differences in SM betweenthe groups. Other differences in the severity of SM were the result of diagnosis and the interaction between diagnosis and an intellectual disability. CONCLUSION. SPD may be a source of SM, but functional connections between these phenomena will need to be tested in future research. Implications for occupational performance are addressed.